2014
DOI: 10.3174/ajnr.a3915
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Microvascular Permeability with Dynamic Contrast-Enhanced MRI for the Differentiation of Primary CNS Lymphoma and Glioblastoma: Radiologic-Pathologic Correlation

Abstract: BACKGROUND AND PURPOSE: Dynamic contrast-enhanced MR imaging can provide in vivo assessment of the microvasculature in intracranial tumors. The aim of the present study was to evaluate the diagnostic performance of dynamic contrast-enhanced MR imaging derived vascular permeability parameters, including the volume transfer constant, the volume of extravascular extracellular space, and the flux rate constant between the extravascular extracellular space and plasma, for the differentiation of primary CNS lymphoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 25 publications
1
69
0
1
Order By: Relevance
“…DTItractography is very helpful for surgical planning and navigational purposes [34] as well as functional MRI [35]. Recent studies with dynamic contrast-enhanced (DCE) perfusion MRI that provides in vivo assessment of tumors microvasculature have shown that this technique may be useful in distinguishing PCNSL from GBM [36]. DCE perfusion imaging offers potential advantage over dynamic susceptibility contrast-enhanced (DSC) perfusion imaging due to its resilience to susceptibility artifact, higher spatial resolution, and 3D acquisition.…”
Section: Discussionmentioning
confidence: 98%
“…DTItractography is very helpful for surgical planning and navigational purposes [34] as well as functional MRI [35]. Recent studies with dynamic contrast-enhanced (DCE) perfusion MRI that provides in vivo assessment of tumors microvasculature have shown that this technique may be useful in distinguishing PCNSL from GBM [36]. DCE perfusion imaging offers potential advantage over dynamic susceptibility contrast-enhanced (DSC) perfusion imaging due to its resilience to susceptibility artifact, higher spatial resolution, and 3D acquisition.…”
Section: Discussionmentioning
confidence: 98%
“…PCNSL has been shown to have lower vascularity and higher permeability than glioblastoma. 7,14,19,20,25 These differences are considered to reflect their histological changes. PCNSL lacks abundant neovascularisation, but grows angiocentrically and tends to cluster around preexisting brain vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral blood volume maps obtained by CT and MR perfusion are useful to identify primary brain tumors or lymphomas. The latter is characterized by the typical leakage in MR perfusion due to higher vascular permeability [15].…”
Section: Discussionmentioning
confidence: 99%